NALAR HISTORIS PERPOLITIKAN KAUM HAWA MASA NABI MUHAMMAD SAW - Wahyu Iryana (IAIN Bengkulu, 2019)
This paper tries to portray the role of women in the socio-political dimension in the era of the early arrival of Islam Islam is a tolerant religion that has given birth to a number of figures of brave women.. Just mention Khadijah Binti Khuwalid, Fatimah Az Zahra, Shafiyyah Binti Abdul Muthollib, Lubabah, Umul Fadhal Binti Harits, Asma Binti Amis (Wife Jafar), Fatimah Binti Khatab (Wife Said Bin Zaid), Sumayyah fighters women who sacrificed to make the nation proud and religion. For Islam, women are not only used as the secondline of life but rather, women can color the joints of life in a wider scope. So prominent is the role of women in the time of Prophet Muhammad SAW, that they were able to give up property for the glory of Islam they deserve to be called